Rasch Models
VIII, 436 p.
Keywords: Thirty-two years after the publication of the legendary 'Rasch book' (Rasch, 1960), the rich literature on the Rasch model and its extensions was scattered in journals and many less accessible sources, including 'grey' literature. When asked by students or junior researchers for references to the Rasch model, it was a typical reaction on the part of the editors to state that it was difficult to name one, or just a few; actually, only a whole list of references differing in notation and level of formal abstraction seemed to meet the request in most cases. Therefore, in 1992 the editors decided to invite a number of outstanding authors in the field of Rasch modeling to contribute to a book presenting the current state of knowledge about Rasch models. The aim was not just to collect a number of papers on the subject, rather to produce a well-organized monograph. To this end, a workshop was held in Vienna from 25 to 27 February 1993 in which, after a process of mutual reviewing, drafts of all chapters were read and discussed by all authors, leading to a more systematic organization of the topics treated in unified notation and terminology. (The workshop was sponsored by the University of Vienna; here, the editors would like to express their thanks, in the name of all contributors, both for the financial support and for the hospitality granted.